The Impact of AI-Driven Tools on Foreign Students’ Chinese Language Acquisition: A Case Study at Southwest University - Muhammad Arif; Aneta Ismail; Muhammad Aqib; Mirajur Rhaman Shaoan; Wazir Ali; Miracle Uzochukwu Okafor (WISE Pendidikan Indonesia, 2025)
This study explores the use of AI-powered tools such as language learning applications, chatbots, adaptive learning systems, and speech recognition software in the context of Chinese language acquisition by international students. Using a qualitative phenomenological approach, the study investigates how fifteen international students at Southwest University engaged with these tools, the challenges they encountered, and how such technologies shaped their linguistic development and cultural integration. Data were gathered through semi-structured interviews, focus group discussions, and reflective journals, and were analyzed thematically. The findings indicate that 80% of participants reported improved speaking confidence, 75% experienced enhanced listening comprehension, and 85% found chatbot-based interactions engaging. However, 65% of students noted insufficient cultural immersion and contextual learning in AI tools. Based on these insights, the study recommends integrating culturally immersive features such as virtual simulations and role-play into AI systems. It concludes that while AI tools can personalize and accelerate language acquisition, their impact can be maximized when aligned with cultural learning, supporting not only proficiency but also meaningful intercultural communication.